Peran Pemangku Kepentingan dalam Pengembangan Klaster Enceng Gondok di Kecamatan Banyubiru - Dwi Lestari; Mohammad Muktiali (Jurnal Wilayah dan Lingkungan, 2017)
Local economic development (LED) is part of regional development concepts which emphasizes the use of local resources and capabilities and cooperation between all components to achieve quality and sustainable development. The LED initiatives could be accomplished through (industrial) business cluster approach. Cluster is basically a grouping of businesses characterized by business commonalities in proximate locations. The cluster growth requires proper role and involvement from the all stakeholders ranging from public to private sectors such as financial institutions, non-governmental organizations, educational institutions and local communities. Water Hyacinth Cluster in Banyubiru Subdistrict of Semarang Regency is of a good example. During its development trajectories, the Water Hyacinth Cluster has faced several problems because of which the call upon multiple stakeholders involvement necessary. This study aims to figure out and measure the effectiveness of the role played by each stakeholder in the observed cluster development. This study uses a mixed method research which combines quantitative and qualitative approaches. The quantitative approach is used to measure the effectiveness of the role played by the stakeholders involved in cluster, and the qualitative approach to assess and figure out the role of stakeholders deeper. The conclusion reveals that the non-government institutions perform the most dominant involvement among the remaining stakeholders. In addition, the role in production input stage is considerably more effective to the overall cluster performance.